2017
DOI: 10.1093/neuonc/nox078
|View full text |Cite
|
Sign up to set email alerts
|

Adult IDH wild-type lower-grade gliomas should be further stratified

Abstract: Adult IDH wild-type lower-grade gliomas are prognostically heterogeneous and do not have uniformly poor prognosis. Clinical information and additional markers, including MYB, EGFR, TERTp, and H3F3A, should be examined to delineate discrete favorable and unfavorable prognostic groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
149
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 178 publications
(155 citation statements)
references
References 36 publications
6
149
0
Order By: Relevance
“…LGGs usually cause poorer prognosis than IDH-mutant LGGs do (Louis et al, 2016). Although our team has demonstrated that not all IDH-wt LGG patients are with poor prognosis (Aibaidula et al, 2017) (in fact, the T1 and T1 contrast images also demonstrated that no obvious destructive effect that similar to HGG was observed in the IDH-wt LGG patients, see Supporting Information Figure S10), we still took measures to control the potential influence of molecular characteristics on the main findings of our research, by excluding the IDHwt LGG patients. Following this procedure, the validation analysis demonstrated that the main findings regarding the different plastic mechanisms of cerebellar ALFF and GMV between LGG and HGG patients were robust.…”
Section: Limitations and Future Directionsmentioning
confidence: 76%
“…LGGs usually cause poorer prognosis than IDH-mutant LGGs do (Louis et al, 2016). Although our team has demonstrated that not all IDH-wt LGG patients are with poor prognosis (Aibaidula et al, 2017) (in fact, the T1 and T1 contrast images also demonstrated that no obvious destructive effect that similar to HGG was observed in the IDH-wt LGG patients, see Supporting Information Figure S10), we still took measures to control the potential influence of molecular characteristics on the main findings of our research, by excluding the IDHwt LGG patients. Following this procedure, the validation analysis demonstrated that the main findings regarding the different plastic mechanisms of cerebellar ALFF and GMV between LGG and HGG patients were robust.…”
Section: Limitations and Future Directionsmentioning
confidence: 76%
“…These conclusions are based on the findings that those histologic IDH-wildtype diffuse astrocytic gliomas of WHO grade II or III that carry EGFR amplification, +7/−10 or TERT promoter mutation are associated with significantly shorter patient survival compared to patients with other WHO grade II or III gliomas, and patients have outcomes similar to patients with IDH-wildtype glioblastoma [1, 2, 11, 26, 27, 32, 33]. The large majority of IDH-wildtype diffuse astrocytic gliomas of WHO grade II or III with these genetic signatures correspond histologically to anaplastic astrocytoma, WHO grade III.…”
Section: Recommended Grading Parameters: Egfr Amplification Combinedmentioning
confidence: 99%
“…Additional studies are needed on clinical outcomes, yet these patients appear to have a favorable prognosis and some may be responsive to targeted therapies. Also deserving of further study are a small group of IDH-wildtype diffuse astrocytic gliomas that harbor MYB/MYBL alterations [1, 24]. Tumors with this single driver genetic alteration occur predominantly in childhood, but have also been described in adults, and have a more indolent clinical course.…”
Section: Caveatsmentioning
confidence: 99%
“…This sensitivity is within the range of allelic fraction noted in a cohort of infiltrative brain tumor specimens previously analyzed by an orthogonal next generation sequencing assay: IDH1 R132 mutations median: 32% (5-52%), TERT promoter mutation: 23% (12-61%), and BRAF V600E: 29% (6-39%) (SI Appendix, Table S3). Detection of one of the mutations confirmed the presence of tumor tissue, and mutual exclusivity of the alterations served as reciprocal internal positive controls to reserve the intraoperative decision for in situ application of NAMPTi to IDH mutant gliomas (26). We validated our assay on 87 clinically annotated brain tumor specimens ( Fig.…”
Section: Development Of Intraoperative Genotyping Diagnostic To Guidementioning
confidence: 99%